The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12879-015-1271-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis of virus-enriched fractions obtained from plasma pools of patients with dengue fever or severe dengue

Abstract: BackgroundDengue is the most widespread mosquito-borne viral disease of public health concern. In some patients, endothelial cell and platelet dysfunction lead to life-threatening hemorrhagic dengue fever or dengue shock syndrome. Prognostication of disease severity is urgently required to improve patient management. The pathogenesis of severe dengue has not been fully elucidated, and the role of host proteins associated with viral particles has received little exploration.MethodsThe proteomes of virion-enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Moreover, dengue patients had increased P-CD62 surface expression on platelets from patients presenting dengue with warning signs and severe dengue syndromes compared to mild dengue. In agreement, they observed exhaustion of the granule-stored chemokine PF4/CXCL4 in platelets from patients with dengue [148], similarly to another study reported that patients with severe dengue have lower levels of PF4/ CXCL4 in plasma when compared to mild dengue patients [149].…”
Section: Platelets As Immune Cellssupporting
confidence: 85%
“…Moreover, dengue patients had increased P-CD62 surface expression on platelets from patients presenting dengue with warning signs and severe dengue syndromes compared to mild dengue. In agreement, they observed exhaustion of the granule-stored chemokine PF4/CXCL4 in platelets from patients with dengue [148], similarly to another study reported that patients with severe dengue have lower levels of PF4/ CXCL4 in plasma when compared to mild dengue patients [149].…”
Section: Platelets As Immune Cellssupporting
confidence: 85%
“…Another study demonstrated that C1q binds directly to both the DENV E protein and the viral particle, and when C1q was pre-incubated prior to DENV infection of THP-1 cells, decreased viral infectivity was observed ( Douradinha et al, 2014 ). Proteomics data confirmed the binding of several complement proteins, including C1q, C1s, C1r, C5, C9, and mannan-binding lectin serine protease 1 (MASP1) on viral-enriched fractions from DENV-infected patients and on domain III of the DENV E protein ( Fragnoud et al, 2015 ; Huerta et al, 2016 ).…”
Section: Complement System and Flavivirusesmentioning
confidence: 76%
“…Fragnoud et al . 43 identified 22 proteins compared proteins purified from plasma pools of dengue fever patients and normal controls. These proteins were analysed by nano-liquid chromatography coupled to ion trap mass spectrometry and identified using data libraries.…”
Section: Methodsmentioning
confidence: 99%